2016
DOI: 10.1155/2016/9895245
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Fullerene Increases NF‐κB Activity and Blocks Genotoxic Effect of Oxidative Stress in Serum‐Starving Human Embryo Lung Diploid Fibroblasts

Abstract: The influence of a water-soluble [60] fullerene derivative containing five residues of 3-phenylpropionic acid and a chlorine addend appended to the carbon cage (F-828) on serum-starving human embryo lung diploid fibroblasts (HELFs) was studied. Serum deprivation evokes oxidative stress in HELFs. Cultivation of serum-starving HELFs in the presence of 0.1–1 µM F-828 significantly decreases the level of free radicals, inhibits autophagy, and represses expression of NOX4 and NRF2 proteins. The activity of NF-κB su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 38 publications
0
20
0
4
Order By: Relevance
“…The role of autophagy in the mechanisms of respiratory disease has been controversial with studies that have suggested both protective and injurious aspects ( Kim et al, 2016 ). Whether autophagy is protective or detrimental in respiratory disease seems to depend on the extent of its activation, specific stimuli/circumstances, and specific cell type ( Ershova et al, 2016 ). Additionally, the autophagic damage of NHBE cells was related to the stimulation time and concentration of CSE.…”
Section: Discussionmentioning
confidence: 99%
“…The role of autophagy in the mechanisms of respiratory disease has been controversial with studies that have suggested both protective and injurious aspects ( Kim et al, 2016 ). Whether autophagy is protective or detrimental in respiratory disease seems to depend on the extent of its activation, specific stimuli/circumstances, and specific cell type ( Ershova et al, 2016 ). Additionally, the autophagic damage of NHBE cells was related to the stimulation time and concentration of CSE.…”
Section: Discussionmentioning
confidence: 99%
“…Approval#5 was obtained from the Committee for Medical and Health Research Ethics of RCMG. Cells were seeded at 1.7 × 10 4 per mL in DMEM (Paneco, Moscow, Russia) with a 10% fetal calf serum (PAA Laboratories, Vienna, Austria), 50 U/mL penicillin, 50-μg/mL streptomycin and 10-μg/mL gentamycin (all the reagents were from Sigma-Aldrich, St. Louis, MO, USA) and cultured at 37 °C for 2 or 24 h as described elsewhere [ 35 , 36 ]. Fullerenes were dissolved under sterile conditions in a minimum volume of sterilized water or a saline solution.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were grown in a 96-well plate for 72 h. Cell viability was assessed with the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay, as described previously [ 35 , 36 ]. The plates were read at 550 nm with EnSpire plate reader (EnSpire Equipment, Turku, Finland).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Approval#5 was obtained from the Committee for Medical and Health Research Ethics of RCMG. Cells were seeded at 1.7 × 104 per ml in DMEM (Paneco, Moscow, Russia) with 10% fetal calf serum (PAA, Vienna, Austria), 50 U/ml penicillin, 50 μ g/ml streptomycin, and 10 μ g/ml gentamycin, and cultured at 37°C for 2 or 24 h as previously described in [13, 14]. Investigated fullerene derivatives were added to the medium, and the cells were cultured for periods ranging from 15 min to 48 h.…”
Section: Methodsmentioning
confidence: 99%